Some aspects of stability and nanophase formation in quasicrystals during mechanical milling - Mukhopadhyay N.K.; Yadav T.P. (My University, 2025)
Non-equilibrium processing and other related techniques can activate quasicrystalline structures to a higher energy level and enable them to attain various stable/metastable structures. During mechanical milling of quasicrystalline alloys, the stability of the complex structures is of immense importance from a scientific and technological point of view. The evolution of nanoquasicrystalline, nanocrystalline, and amorphous phases and their composites has been observed in the course of milling. The experimental results for mechanical alloying of elemental powders (required for the synthesis of quasicrystals) and mechanical milling of quasicrystals are discussed. The salient features observed in quasicrystals during other non-equilibrium processing are highlighted. Nanospinel formation from the Al-based quasicrystalline precursor is mentioned. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.